Force-velocity vs. power-velocity relationships: Which method provides the maximum power and optimal velocity with higher reliability during the leg cycle-ergometer and bench press throw exercises? - Pérez-Castilla, A.; García-Ramos, A. (Measurement in Physical Education and Exercise Science, 2021)
An a-posteriori multicentre reliability study was conducted to compare the reliability and magnitude of the maximum power (Pmax) and optimal velocity (Vopt) between the force-power-velocity relationships during the leg cycle-ergometer and bench press throw exercises. The force-power-velocity relationships were determined in two separate sessions considering the values of force, velocity, and power collected under multiple loads. The force-velocity relationship was also determined from the force and velocity values collected under only the two most distant loads. Reliability of all regression models was high for Pmax and Vopt during the leg cycle-ergometer (CVrange: 1.73-2.98%) and for Pmax during the bench press throw (CVrange: 4.47-4.73%), while the reliability was acceptable for Vopt during the bench press throw (CVrange: 6.52-7.34%). Significant differences between the force-power-velocity relationships were observed for both Pmax and Vopt (P <.001). All regression models can be confidently used to determine Pmax and Vopt, but these should not be used interchangeably.